Obesity and Pulmonary Hypertension: A Review of Pathophysiologic Mechanisms. (3rd September 2012) - Friedman, Scott E.; Andrus, Bruce W.
Abstract : Pulmonary hypertension (PH) is a potentially life-threatening condition arising from a wide variety of pathophysiologic mechanisms. Effective treatment requires a systematic diagnostic approach to identify all reversible mechanisms. Many of these mechanisms are relevant to those afflicted with obesity. The unique mechanisms of PH in the obese include obstructive sleep apnea, obesity hypoventilation syndrome, anorexigen use, cardiomyopathy of obesity, and pulmonary thromboembolic disease. Novel mechanisms of PH in the obese include endothelial dysfunction and hyperuricemia. A wide range of effective therapies exist to mitigate the disability of PH in the obese.